Adult Goat Retinal Neuronal Culture: Applications in Modeling Hyperglycemia - Sharma, Sapana; Chakravarthy, Harshini; Suresh, Gowthaman; Devanathan, Vasudharani (Frontiers in Neuroscience, 2019)
Culture of adult neurons of the central nervous system (CNS) can provide a unique model system to explore neurodegenerative diseases. The CNS includes neurons and glia of the brain, spinal cord and retina. Neurons in the retina have the advantage of being the most accessible cells of the CNS, and can serve as a reliable mirror to the brain. Typically, primary cultures utilize fetal rodent neurons, but very rarely adult neurons from larger mammals. Here, we cultured primary retinal neurons isolated from adult goat up to 10 days, and established an in vitro model of hyperglycemia for performing morphological and molecular characterization studies. Immunofluorescence staining revealed that approximately 30–40% of cultured cells expressed neuronal markers. Next, we examined the relative expression of cell adhesion molecules (CAMs) in adult goat brain and retina. We also studied the effect of different glucose concentrations and media composition on the growth and expression of CAMs in cultured retinal neurons. Hyperglycemia significantly enhances neurite outgrowth in adult retinal neurons in culture. Expression of CAMs such as Caspr1, Contactin1 and Prion is downregulated in the presence of high glucose. Hyperglycemia downregulates the expression of the transcription factor CCAAT/enhancer binding protein (C/EBP α), predicted to bind CAM gene promoters. Collectively, our study demonstrates that metabolic environment markedly affects transcriptional regulation of CAMs in adult retinal neurons in culture. The effect of hyperglycemia on CAM interactions, as well as related changes in intracellular signaling pathways in adult retinal neurons warrants further investigation.